Investigation of the influence of fermentation conditions on the content of biologically active substances of the phenolic complex in young red wines - L. V. Gnetko; L. P. Nerovnykh; Kh. R. Siyukhov; G. Yu. Arutyunova (Новые технологии, 2023)
The article presents data on the study of the influence of fermentation conditions on the content of biologically active substances of the phenolic complex in young red wines.Red wines, due to the high content of phenolic substances in them, have P-vitamin activity, antiglycemic, antihepatoxic and antimutagenic effects, as well as antimicrobial and other types of biological activity. Many of the phenolic substances act as natural antioxidants, have a radical-cleansing ability, and help reduce blood cholesterol levels. Thanks to these properties, red wines contribute to the prevention of many diseases and correct the antioxidant status of a person.The objects of the research are wine materials obtained from grapes of the Moldova variety by the method of carbon dioxide maceration, with a process duration of 4 days or 7 days. In the second case, additional introduction of carbon dioxide of exogenous origin hasa been used. As a control one, wine material obtained by traditional technology has been used, as a result of must fermentation on pulp with a floating cap.The influence of fermentation conditions on the total content of monomeric and polymeric phenolic compounds, as well as on the mass concentration of individual phenolic acids and flavonoids, has been studied.It has been established that an increase in the duration of maceration of a bunch of grapes up to 7 days, as well as the additional introduction of CO2 of exogenous origin, have contributed to the intensification of extraction processes and led to a natural increase in the concentration of substances of the phenolic complex.Thus, the possibility of using carbon dioxide maceration, which ensures the optimal accumulation of substances of the phenolic complex, has been established for the production of young red table wines, especially when processing high-acid grape varieties with a high content of anthocyanins and tannin. Carrying out carbon dioxide maceration of whole bunches of grapes under conditions of anaerobiosis has contributed to the preservation of biologically active substances in wine, including vitamins, stilbenes, phenolcarboxylic acids.